Clomiphene citrate reduces premature LH surge in obese women during controlled ovarian stimulation: a retrospective cohort study - Zeng, Yuqi; Huang, Yuting; Liu, Yali; Shen, Xi; Nie, Yunhan; Wang, Li; Kuang, Yanping (Frontiers in Endocrinology, 2025)
BackgroundClomiphene citrate effectively suppressed the negative feedback of estrogen on the hypothalamus and induces premature luteinizing hormone (LH) surge during controlled ovulation stimulation, while obese women often have impaired hypothalamic-pituitary function. This study aimed to investigate whether the utilization of clomiphene citrate for controlled ovulation stimulation in obese women can effectively decrease the likelihood of premature LH surge.MethodsA retrospective study was conducted on women under the age of 38 with normal menstrual cycles and ovarian reserve who underwent controlled ovulation stimulation (COH) using clomiphene citrate. The participants were categorized by the Asian body mass index (BMI) classification. The dynamic reproductive endocrinological profiles during COH, especially the probability of serum LH concentration exceeding 10 IU/L, as well as the outcomes related to the embryo development and pregnancy, were compared among three BMI groups.ResultsThe basal levels of LH exhibited a significant reduction in overweight and obese women (p<0.001). Additionally, there was a significant decrease in the incidence of LH concentration exceeding 10 IU/L during controlled ovulation stimulation among overweight and obese women (7.19% vs 3.62% vs2.27%, p<0.05). Moreover, there were no significant differences observed among the three BMI groups regarding embryo transfer numbers, implantation, pregnancy or live birth rates.ConclusionsIn obese women, clomiphene citrate effectively controlled LH levels, resulting a low prevalence of premature LH surge compared to patients with normal weight. This evidence contributes to a safer and more effective treatment for infertility in obese individuals.